Preimplantation factor modulates oligodendrocytes by H19-induced demethylation of NCOR2 - Marialuigia Spinelli; Celiné Boucard; Sara Ornaghi; Andreina Schoeberlein; Keller Irene; Daniel Coman; Fahmeed Hyder; Longbo Zhang; Valérie Haesler; Angelique Bordey; Eytan Barnea; Michael Paidas; et al. (JCI Insight, 2021)
Failed or altered gliogenesis is a major characteristic of diffuse white matter injury in survivors of premature birth. The developmentally regulated long noncoding RNA (lncRNA) H19 inhibits S-adenosylhomocysteine hydrolase (SAHH) and contributes to methylation of diverse cellular components, such as DNA, RNA, proteins, lipids, and neurotransmitters. We showed that the pregnancy-derived synthetic PreImplantation Factor (sPIF) induces expression of the nuclear receptor corepressor 2 (NCOR2) via H19/SAHH-mediated DNA demethylation. In turn, NCOR2 affects oligodendrocyte differentiation markers. Accordingly, after hypoxic-ischemic brain injury in rodents, myelin protection and oligodendrocytes’ fate are in part modulated by sPIF and H19. Our results revealed an unexpected mechanism of the H19/SAHH axis underlying myelin preservation during brain recovery and its use in treating neurodegenerative diseases can be envisioned.